Self-saturation of amplified spontaneous emission in a fiber amplifier - M.A. Mahdi,; S. Thirumeni,; P. Poopalan, (Universiti Kebangsaan Malaysia, 2001)
The dependence of erbium-doped fiber amplifier (EDFA) performance on amplifier self-saturation is studied by tuning the pump wavelength over a 5 nm band centered at 980 nm. Gain and noise figure are degraded at the peak pump absorption wavelength, which shows the strongest effect of amplifier self-saturation. It is shown experimentally that tuning the pump wavelength away from the peak pump absorption provides 1 -2 dB improvement in pump to-signal conversion. The effect of amplifier self-saturation is also dependent on the signal wavelength where high gain and noise figure penalties are obtained at 1530 nm (± 5 nm) band.